2019
DOI: 10.3389/fneur.2019.00140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Therapy Practice at Home and in the Clinic: A Retrospective Analysis of the Constant Therapy Platform Data Set

Abstract: Background: Computer-based therapies can provide an affordable and practical alternative by providing frequent intervention for stroke survivors with chronic aphasia by allowing the opportunity for home exercise practice, however more evidence is needed. The goal of this retrospective analysis was to compare the time course of therapy engagement when therapy was targeted in the clinic or at home by post-stroke individuals. We examined if home users of the therapy were compliant in therapy and if thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…These results provide preliminary evidence for the usefulness of a tablet-based platform to deliver tailored language and cognitive therapy to individuals with aphasia. Godlove et al 20 N=3686 Retrospective analysis United States Constant Therapy Language/speech and cognitive skills To examine if home users of the therapy were compliant in therapy and if this documented practice time was associated with improved outcomes similar to clinic patients who practiced under the guidance of a clinician. Outcomes of treatment are similar for home users and clinic patients, indicating the potential usability of a home-based treatment program for rehabilitation for poststroke aphasia.…”
Section: Resultsmentioning
confidence: 99%
“…These results provide preliminary evidence for the usefulness of a tablet-based platform to deliver tailored language and cognitive therapy to individuals with aphasia. Godlove et al 20 N=3686 Retrospective analysis United States Constant Therapy Language/speech and cognitive skills To examine if home users of the therapy were compliant in therapy and if this documented practice time was associated with improved outcomes similar to clinic patients who practiced under the guidance of a clinician. Outcomes of treatment are similar for home users and clinic patients, indicating the potential usability of a home-based treatment program for rehabilitation for poststroke aphasia.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, none of these apps focused on the usability of the apps in providing caregiving support, which is similar to the other reviews conducted (Bender et al, 2013; Giunti et al, 2018; Mobasheri et al, 2014) Instead, they focused on evaluating the accuracy of the app in improving recovery and user satisfaction. Accuracy in these apps was evaluated either through pilot trials (Sarfo et al, 2018), control studies (Blanquero et al, 2019; Godlove et al, 2019; Zickefoose et al, 2013), by validating the output through medical‐grade devices (Proesmans et al, 2019) or by validation using available datasets (Parmar et al, 2015), while satisfaction was assessed using a 5‐point Likert rating scale (Sarfo et al, 2018). Furthermore, outcomes from these studies demonstrated that users accessing these apps were shown to have significant improvement in managing tasks (Godlove et al, 2019), improved performance (Blanquero et al, 2019; Sarfo et al, 2018; Zickefoose et al, 2013), ability to identify risks (Parmar et al, 2015) and ability to monitor heart risk factor without the need for medical‐grade devices (Proesmans et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All the participants were involved in a 10-week treatment study that used a tablet-based language therapy application, Constant Therapy, a research-based language rehabilitation program devised by researchers at Boston University that incorporates tasks to address many domains of language and has been used in research studies investigating aphasia rehabilitation (Constant Therapy, Inc., Newton, MA, USA) ( 14 , 15 , 44 , 52 ). Constant Therapy was selected because it allows for the tracking of response latency, cue use, and response accuracy, measures that enabled us to evaluate behaviors both in the clinic and during home practice.…”
Section: Methodsmentioning
confidence: 99%
“…Beyond circumventing these constraints, such therapies can be leveraged to increase the intensity of treatment as they are accessible from any setting at any time (1,(6)(7)(8)(9)(10)(11)(12). Furthermore, even when therapy is administered remotely, clinicians are able to monitor progress and tailor therapy to a client's unique needs (4,5,8,(13)(14)(15). Recent work by Kiran et al (16) demonstrated that utilizing tablet-based language rehabilitation can simultaneously increase the intensity of practice while also tailoring treatment to the individual participant's needs.…”
Section: Introductionmentioning
confidence: 99%